Pemodelan Endapan dan Estimasi Sumberdaya Batubara dengan Block Model di PT Batubara Jambi Lestari Kecamatan Mestong Kabupaten Muaro Jambi - Yulian Aliffano; Yudi Arista Yulanda; Muhammad El Hakim (Universitas Halu Oleo, 2025)
Jambi Province holds significant potential in energy and mineral resources, particularly coal, part of which has been exploited while others are still under exploration. PT Batubara Jambi Lestari plans to develop an open-pit mine in the northern block of its IUP-OP area, necessitating deposit modelling and coal resource estimation as the basis for mine planning. Thus far, coal modelling has generally relied on stratigraphic models for geological interpretation, whereas the application of block models to coal deposits remains limited. This study seeks to address this gap by examining the use of block models in coal deposit modelling. Resource estimation was conducted using the Nearest Neighbour Point (NNP) method, selected due to its suitability for relatively homogeneous coal deposits, computational efficiency, and minimal bias against local variability. The research focused on the northern block of the Muara Enim Formation, the main coal-bearing formation, with modelling carried out through correlation between drill holes. The resulting model illustrates a deposit shaped like a horse back, characterized by coal seams and sediments arching upward due to compressional forces, with an average dip of 12°. The application of the block model required manual adjustments through a trial-and-error approach to ensure consistency with the geological database, but it successfully represented the geological conditions. The estimation results indicate a measured coal resource of 2,013,750 tons, which provides an important reference for mine planning at PT Batubara Jambi Lestari.